Exploring the lived experiences of mental health professionals: A phenomenological study on ligature training in a simulated environment (Journal of Applied Learning and Teaching, 2024)
This phenomenological study investigates the first-hand experiences of mental health practitioners engaged in an intensive two-day workshop on managing ligature-related situations. This workshop was implemented within a realistic simulated environment at a renowned higher education institution, offering participants a chance to experience scenarios that closely mirror real-world conditions.In this study, a rigorous thematic analysis was applied to participants’ feedback, which yielded three dominant themes: (1) transformative experience, (2) transformed views about ligature training, and (3) patient-centred risk management and empowerment. The first theme encapsulates the idea of a ‘transformative learning journey.’ Participants experienced a marked expansion in their knowledge base, practical skills, and overall understanding of ligature management following their participation. The training, facilitated by realistic simulations, demonstrated the efficacy of such an immersive approach in enhancing healthcare professionals’ competency in handling ligature-related situations. The second theme, ‘transformed views about ligature training,’ alludes to the substantial shift in the participants’ pre-existing attitudes towards such training workshops. Post-participation, their views were radically altered as they acknowledged the profound value and potential life-saving benefits such immersive training can impart, particularly in the critical sphere of ligature management. The third theme emphasises ‘patient-centred risk management and empowerment.’ This underlines the central role that patients play in the approach towards managing ligature-related situations. An essential takeaway from the training was the need for healthcare professionals to manage risks effectively and instil a sense of empowerment within their patients, thereby promoting them as active participants in their care journey.This research provides a comprehensive exploration of the lived experiences of mental health professionals within a simulated learning environment. Rather than solely recounting the training process and participants’ immediate reactions, it probes the training’s more profound, lasting impact on the attendees’ professional lives and perspectives. Consequently, the study significantly contributes to the existing knowledge in ligature training and care for people at risk or post-ligature, accentuating the effectiveness of simulation-based educational methodologies. It offers invaluable guidance for healthcare institutions and educators looking to design or improve their training strategies, thus equipping professionals to tackle ligature-related situations effectively and compassionately.